Socially Responsible Investment und umweltorientiertes Venture Capital - Alexis Figeac (Fachhochschule für Wirtschaft Berlin, IMB Institute of Management Berlin, 2007)
Socially Responsible Investors are concerned about social, ethical and especially environmental issues in enterprises. They invest mostly through investment vehicles officially labelled SRI funds, or if not, then with clear mandates to their investment managers to invest responsibly. The investment universe of such funds and managers is usually limited to publicly-listed enterprises. Yet innovation and especially those in the environment sector occur in young, non-quoted companies. Venture Capital can play a vital role in financing innovations in environmental and clean energy technologies. This is a departure from traditional Venture Capital and is seen as such by the investment community, thereby withholding allocations to such Venture Capital initiatives. Who better then, than Socially Responsible Investors to provide capital to environment-oriented VC funds?
Keywords: 650